Development of Superior Cattle Breeding Center and Forage Animal Feed (BPTU-HPT) Padang Atas Regency of Fifty Cities (2011-2020). - Gesi Putri Yenti; Etmi Hardi (Jurusan Sejarah FIS UNP, 2022)
This study discusses the Development of Superior Cattle Breeding Center and Forage Animal Feed (BPTU-HPT) Padang Mengatas Regency of Fifty Cities (2011-2020). The research problem is formulated as follows: (1) How is the development of BPTU-HPT Padang Mengatas in 2011-2020. (2) How BPTU-HPT Padang Mengatas transformed into tourism and education-based farms. This writing aims to explain the development of BPTU-HPT Padang Mengatas in 2011-2020 and describe BPTU-HPT Padang Mengatas as a tourism and education-based farm. This research includes historical qualitative research, therefore research on the Development of Superior Cattle Breeding Center and Forage Animal Feed (BPTU-HPT) Padang Mengatas Regency of Fifty Cities (2011-2020) uses the historical method with the following steps: (1) heuristics, collecting various data from primary sources through interviews with historical actors, archives and observations, while secondary sources obtained from written sources in the form of theses, journals and articles, and several documents published in the form of performance reports of BPTU-HPT Padang Mengatas published by the Ministry of Agriculture RI, as well as interviews with historical witnesses, namely the Mungo community, (2) source criticism, (3) analysis, (4) historiography, namely historical writing. From the discussion, it can be seen that; First, BPTU-HPT Padang Mengatas experienced development in terms of livestock husbandry, management, and marketing of livestock after the land process was completed, namely in 2012. Second; BPTU-HPT Padang Mengatas besides being a center for breeding superior livestock and animal feed, it is also used as educational farm -based and a tourism. Abstrak Penelitian ini membahas tentang Perkembangan Balai Pembibitan Ternak Unggul dan Hijauan Pakan Ternak (BPTU-HPT) Padang Mengatas Kabupaten Lima Puluh Kota (2011-2020). Permasalahaan penelitian dirumuskan sebagai berikut: (1) Bagaimana perkembangan BPTU-HPT Padang Mengatas tahun 2011-2020. (2) Bagaimana BPTU-HPT Padang Mengatas bertransformasi menjadi peternakan berbasis wisata dan edukasi. Penulisan ini bertujuan untuk menjelaskan perkembangan BPTU-HPT Padang Mengatas tahun 2011-2020 serta mendeskripsikan BPTU-HPT Padang Mengatas sebagai peternakan berbasis wisata dan edukasi. Penelitian ini termasuk penelitian kualitatif sejarah, oleh karena itu peneltian tentang Perkembangan Balai Pembibitan Ternak Unggul dan Hijauan Pakan Ternak (BPTU-HPT) Padang Mengatas Kabupaten Lima Puluh Kota (2011-2020) menggunakan metode sejarah dengan langkah-langkah sebagai berikut: (1) heuristik, pengumpulan berbagai data dari sumber primer melalui wawancara dengan pelaku sejarah, arsip dan observasi, sedangkan sumber sekunder diperoleh dari sumber tertulis berupa skripsi, jurnal dan artikel, dan beberapa dokumen yang diterbitkan berupa laporan kinerja BPTU-HPT Padang Mengatas yang diterbitkan oleh Kementerian Pertanian RI, serta wawancara dengan saksi sejarah yaitu dengan masyarakat Mungo, (2) kritik sumber, (3) analisis, (4) historiografi, yaitu penulisan sejarah. Dari pembahasan yang dilakukan dapat diketahui bahwa; Pertama sejak tahun 2012 hingga tahun 2020 BPTU- BPTU-HPT Padang Mengatas mengalami perkembangan baik dari segi peternakan, pengelolaan, maupun pemasaran ternak. Kedua; BPTU-HPT Padang Mengatas selain pusat pembibitan ternak unggul dan pakan ternak juga dijadikan sebagai peternakan berbasis edukasi dan wisata.